2021
DOI: 10.3389/fpubh.2021.682341
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Dysmenorrhea in Women Exposed to Higher Concentrations of NO, NO2, NOx, CO, and PM2.5: A Nationwide Population-Based Study

Abstract: Background: Air pollution is speculated to affect the reproductive health of women. However, a longitudinal association between exposure to air pollution and dysmenorrhea has not been identified, which this study aimed to examine this point.Methods: Two nationwide databases, namely the Taiwan Air Quality Monitoring database and the Taiwan National Health Research Institutes database were linked. Women with a history of dysmenorrhea (International Classification of Disease, Ninth Revision, Clinical Modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
4
0
1
Order By: Relevance
“…[15] A WHO systematic review of dysmenorrhea reported that the incidence of dysmenorrhea was 16-81% [16]. Recent studies determined the prevalence of dysmenorrhea from 45-95% of menstruating women [3]. According to the results, the current study demonstrates that (51.5%) of the students experienced dysmenorrhea.…”
Section: Results and Dissectionsmentioning
confidence: 50%
See 1 more Smart Citation
“…[15] A WHO systematic review of dysmenorrhea reported that the incidence of dysmenorrhea was 16-81% [16]. Recent studies determined the prevalence of dysmenorrhea from 45-95% of menstruating women [3]. According to the results, the current study demonstrates that (51.5%) of the students experienced dysmenorrhea.…”
Section: Results and Dissectionsmentioning
confidence: 50%
“…Women experience a variance of physical and psychological symptoms during menstruation, including pain, headache, and lethargy [2]. Dysmenorrhea is a common symptom in adolescent women which can affect between 45-95% of menstruating ones [3]. However, prevalence estimates vary widely due to methodological and cultural differences that may limit the generalizability of international estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Физиологическая роль данных веществ состоит в обеспечении менструальной реакции за счет следующих эффектов [18]: ■ сокращение спиральных артериол, приводящее к ишемии и отторжению эндометрия; ■ сокращение мышц тела матки; ■ расслабление мышц шейки матки. На образование, высвобождение и утилизацию простагландинов влияют многочисленные факторы: стимуляция нервов, гипоксия, механическое растяжение органа, уровень половых гормонов, экология [19]. Воздействие указанных факторов в случае дисменореи может привести к росту уровня простагландинов, неадекватному для физиологического течения менструации, и соответственно к более тяжелому течению дисменореи.…”
Section: патогенез первичной дисменореи: роль простагландиновunclassified
“…Contrarily, dysmenorrhea is a common menstrual symptom, affecting 45-95% of menstruating women [7]. A person's daily activities, academic and professional performance, social life, and quality of life can all be impacted by painful periods [8].…”
Section: Introductionmentioning
confidence: 99%